ANALYSIS OF DEFINITIONS OF THE CONCEPT "DISCOURSE" IN LINGUISTICS (American Journal of Research in Humanities and Social Sciences, 2023)
In this article is discussed and analyzes the definitions given to the idea, of language in linguistics. At the same time, ideas about the language given by European and Russian scientists were generalized and deeply analyzed. In linguistics, the term "discourse" has been used since ancient times. It is safe to say that the problem of defining this term has attracted the attention of scientists since the middle of the 20th century. The main problem of researchers is to determine the place of this explanation on the border of many scientific disciplines with different objects of study: sociology, psychology, political science, logic, ethnography, philosophy, literary criticism, stylistics, linguistics, etc. Therefore, today the term "discourse" does not have a single generally accepted definition.